2017
DOI: 10.1186/s12885-017-3683-9
|View full text |Cite
|
Sign up to set email alerts
|

The relative risk of second primary cancers in Austria’s western states: a retrospective cohort study

Abstract: BackgroundCancer survivors are at risk of developing a second primary cancer (SPC) later in life because of persisting effects of genetic and behavioural risk factors, the long-term sequelae of chemotherapy, radiotherapy and the passage of time. This is the first study with Austrian data on an array of entities, estimating the risk of SPCs in a population-based study by calculating standardized incidence ratios (SIRs).MethodsThis retrospective cohort study included all invasive incident cancer cases diagnosed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 31 publications
5
17
0
Order By: Relevance
“…In line with other studies [11,13,17,35], we found a consistent pattern of higher risks of SPC for youngonset patients. Notably, longer residual life expectancy itself is insufficient to explain our results as we calculated age-adjusted risks.…”
Section: Discussion In the Context Of The Literaturesupporting
confidence: 93%
See 2 more Smart Citations
“…In line with other studies [11,13,17,35], we found a consistent pattern of higher risks of SPC for youngonset patients. Notably, longer residual life expectancy itself is insufficient to explain our results as we calculated age-adjusted risks.…”
Section: Discussion In the Context Of The Literaturesupporting
confidence: 93%
“…In line with other studies outside of Switzerland [35,40], we observed a significantly reduced risk of SPC for prostate cancer survivors. Prostate cancer is the most common cancer in males, leading to high numbers of expected cases.…”
Section: Discussion In the Context Of The Literaturesupporting
confidence: 93%
See 1 more Smart Citation
“…We identified one additional article by manually searching the references of the included articles (Chan, Gooi, Mydlarz, & Agrawal, 2016). A total of 26 studies (Boakye et al., 2018, 2019; Chan et al., 2016; Chen et al., 2008, 2011; Chow, Au, Mang, Cheung, & Risk, 2019; Chuang et al., 2008; Cianfriglia, Di Gregorio, & Manieri, 1999; Dikshit et al., 2005; Dong & Hemminki, 2001; Goggins et al., 2010; Jégu, Binder‐Foucard, Borel, & Velten, 2013; Jung, Lim, Jung, Ryu, & Won, 2015; Lee, Wang, Lu, Huang, & Chen, 2017; Levi, Randimbison, & Te, 2003; Levi, Te, Randimbison, Maspoli, & La Vecchia, 2006; Min et al., 2019; Morris, Sikora, Hayes, Patel, & Ganly, 2011; Neumann et al., 2016; Ooft & van Ipenburg, 2016; Preyer, Concin, Obermair, Concin, & Ulmer, 2017; Scélo et al., 2007; Sikora et al., 2009; Söderholm et al., 1994; Suk et al., 2018; Warnakulasuriya et al., 2003) met the eligibility criteria for this systematic review.…”
Section: Resultsmentioning
confidence: 99%
“…The main characteristics of the studies are shown in Table 1. Seventeen studies (77%) were carried out in the Western countries (eleven in Europe Cianfriglia et al., 1999; Dikshit et al., 2005; Dong & Hemminki, 2001; Jégu et al., 2013; Levi et al., 2003; Levi et al., 2006; Neumann et al., 2016; Ooft et al, 2016; Preyer et al., 2017; Söderholm et al., 1994; Warnakulasuriya et al., 2003), six (Boakye et al., 2018, 2019; Chan et al., 2016; Morris, Sikora, Hayes, et al, 2011; Sikora et al., 2009; Suk et al., 2018) in USA and three (Chuang et al., 2008; Dikshit et al., 2005; Scélo et al., 2007) were multicentre collaborations across Europe, Canada and Australia), and seven studies (22.7%) were conducted in Asian population (Taiwan [Chen et al., 2008;Chen et al., 2011;Lee et al., 2017], China [Chow et al., 2019;Goggins et al., 2010] and South Korea [Jung et al., 2015;Min et al., 2019]). Except three studies (Chow et al., 2019; Cianfriglia et al., 1999; Goggins et al., 2010) that used hospital‐based cancer registries, the other studies used population‐based cancer registries.…”
Section: Resultsmentioning
confidence: 99%